THE EFFECTIVENESS OF BAKING SODA (Sodium Bicarbonate) 20%, 40%, AND 60% ON TEETH THAT HAVE COFFEE STAIN - Hartanto Endrowahyudi; Asih Rahaju; Maria Margareta Dian Puspita (Journal of Health and Dental Sciences, 2023)
Coffee consumption can cause extrinsic discoloration. A treatment that can be done to improve tooth discoloration is bleaching. Bleaching procedures can be carried out using alternative materials that do not cause side effects on dental and oral health, such as baking soda (sodium bicarbonate). This study aims to determine the effectiveness of baking soda 20%, 40%, and 60% on teeth that were discolored by coffee. The study used experimental research with a pretest-posttest group design with a total of 27 premolars study samples divided into three treatment groups: soaking the teeth in a solution of baking soda 20%, 40%, and 60%. Measurement of tooth discoloration using the VITAPAN® Classical Shade guide. Data analysis using the One-Way Anova test followed by post-hoc Tukey analysis. The results showed a significant change in tooth color between the three immersion groups, namely the group with the concentration of baking soda 20%, 40%, and 60% with p=0.012 (p<0.05). A 60% baking soda solution was more effective in whitening teeth with coffee discoloration than 20% and 40%, respectively. DOI : 10.54052/jhds.v2n3.p467-478